Zobowiązania emerytalne w ESA 2010 - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of the research paper was to analyze the methodology of pension liabilities within the European System of Accounts ESA 2010. In order to achieve the goal, the author analyzed: i consequences of the introduction of the ESA 2010, ii methodology for pension liabilities, iii relationship between public debt and hidden public debt. The study positively verified the research hypotheses: i the ESA 2010 will have an impact on the amount of GNI and GDP — ESA 2010 introduces significant changes which in the case of Poland mean increase in GDP in 2013 by 1.6% of which 0.8% are illegal activities; ii the ESA 2010 introduces new regulations in the area of pension liabilities — new regulations in the presentation of pension liabilities draw attention to the impact of pension liabilities on public finances.
Keywords: Europejski System Rachunków Narodowych i Regionalnych (ESA); zobowiązania emerytalne; dług jawny; dług ukryty